2016
DOI: 10.1038/srep29595
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity in young children and their parents–An Early STOPP Sweden–China comparison study

Abstract: Understanding about socio-cultural differences in physical activity in children with high and low risk for obesity can help tailor intervention programs in different settings. This study aimed to compare objectively measured physical activity in two-year-olds and their parents, living in Stockholm, Sweden, and Wuhan, China. Data from Early STOPP was used. Children and parents wore an accelerometer in connection with the child’s second birthday. Weekly and hourly patterns were examined. Correlation between chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 45 publications
3
19
0
Order By: Relevance
“…Nevertheless, disparities have been found in the literature in this respect. For example, the results described by Rodrigues et al [15], as well as those described by Fuemmeler et al [52], showed that children were more likely to engage in physical activity if both parents or the parent who shared sex with them was active, whereas other studies revealed results more similar to those found in our research, showing a greater relationship between the physical activity of the child and the influence of the father [53,54]. This fact reinforces the theory that physical activity is culturally assumed as a masculine domain.…”
Section: Discussionsupporting
confidence: 83%
“…Nevertheless, disparities have been found in the literature in this respect. For example, the results described by Rodrigues et al [15], as well as those described by Fuemmeler et al [52], showed that children were more likely to engage in physical activity if both parents or the parent who shared sex with them was active, whereas other studies revealed results more similar to those found in our research, showing a greater relationship between the physical activity of the child and the influence of the father [53,54]. This fact reinforces the theory that physical activity is culturally assumed as a masculine domain.…”
Section: Discussionsupporting
confidence: 83%
“…We also did not take into account differences in the duration of daytime vs. nighttime interaction between parents and children on weekdays. Such work has been reported ( Fuemmeler, Anderson & Masse, 2011 ; Johansson et al, 2016 ), but comparing that work to ours is difficult and potentially misleading because of substantial differences in the subjects and in mediating factors present.…”
Section: Discussionmentioning
confidence: 62%
“…In cases where more than one article presented baseline data on the same sample of children (Melbourne InFANT Program [23], GET UP! [24], POI [25], IDEFICS [26], Generation R [27], Early STOPP [28], and PREPS [29]), the article with the largest sample size and/or most accurately reflected full day movement behaviours was included.…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…Studies were conducted in 16 different countries, including 8 in the United States [36][37][38][39][40][41][42][43], 4 in Canada [29,[44][45][46] and Australia [23,24,47,48], 2 in China [28,49] and Sweden [26,28], and 1 in Belgium [26], Estonia [26], Germany [26], Hungary [26], Italy [26], Malawi [50], the Netherlands [27], New Zealand [25], Spain [26], Switzerland [33], and Taiwan [51] (note that one study was conducted in both China and Sweden [28] and one study was conducted in Belgium, Estonia, Germany, Hungary, Italy, Spain, and Sweden [26]). The mean sample size of included studies was 142 children (range = 7 to 568), and all studies were published in 2011 or later (88% since 2015).…”
Section: Study Characteristics and Quality Of Included Articlesmentioning
confidence: 99%